INITIAL GROWTH OF Amburana cearensis (Allem.) A. C. Smith IN AN AGROFORESTRY SYSTEM IN THE BRAZILIAN SEMIARID - Pimentel, João Vianey Fernandes (2015)
Amburana cearensis (Allem.) A. C. Smith is a Brazilian semiarid region native plant. It presents good quality wood, contains an active ingredient that can be used for food, perfume and medicine production and it is also a forage and a melifera plant. The responses of the studied species to organic fertilizer and mulch, inputs produced and cycled within its ecosystem are still unknown. For this, an experiment was conducted to study the behavior of seedlings in an agroforestry system intercropped with maize and beans, testing different levels of organic matter (0, 15  and 30 L of manure) with and without soil mulch. It was evaluated the plant height, stem diameter, leaf number, leaf area and the survival of plants in the field one year after planting. The performance of A. cearensis was indifferent to the use of mulch and well adapted to low soil organic matter conditions, obtaining the largest growth in the absence of organic matter.